2011
DOI: 10.1111/j.1755-3768.2011.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and contrast sensitivity after posterior lamellar keratoplasty

Abstract: . Purpose:  It has previously been reported that patients who suffer from Fuchs’ endothelial dystrophy (Fuchs’ ED) have decreased contrast sensibility threshold. The removal of endothelial guttata by Descemet’s Stripping Automated Endothelial Keratoplasty (DSAEK) surgery has also been demonstrated to decrease intraocular light scatter and improve contrast thresholds. The purpose of this study was to compare different visual qualities in patients that had undergone DSAEK surgery in one eye while having untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Recent studies have shown that guttae evoke forward light scatter and cause visual impairment. 41,42 After DSAEK, forward light scatter remained greater in eyes with Fuchs' endothelial corneal dystrophy than in normal eyes and was correlated with recipient visual acuity. 41 Eyes with Fuchs' endothelial corneal dystrophy that underwent DSAEK had improved contrast sensitivity compared with other untreated eyes despite no difference in the standard Snellen visual quality.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have shown that guttae evoke forward light scatter and cause visual impairment. 41,42 After DSAEK, forward light scatter remained greater in eyes with Fuchs' endothelial corneal dystrophy than in normal eyes and was correlated with recipient visual acuity. 41 Eyes with Fuchs' endothelial corneal dystrophy that underwent DSAEK had improved contrast sensitivity compared with other untreated eyes despite no difference in the standard Snellen visual quality.…”
Section: Discussionmentioning
confidence: 94%
“…Nielsen and Hjortdal measured BSCVA and contrast sensitivity in patients following DSAEK who had untreated Fuchs' endothelial dystrophy in the fellow eye. In a patient's questionnaire, they found an explicit preference of the DSAEK eye most likely due to improved contrast sensitivity as BSCVA nearly was the same in both eyes (Nielsen & Hjortdal 2011). But, nevertheless, improvement of BSCVA contributes to patient's satisfaction and is a main purpose in treating endothelial diseases.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6 In patients with Fuchs dystrophy, even when visual acuity is controlled for by statistical methods, there is an improved contrast sensitivity in eyes that have undergone DSAEK as compared with those that have not had surgery. 7,8 Despite the improvement in vision compared with Fuchs dystrophy, a meta-analysis performed by the American Academy of Ophthalmology demonstrated that best-corrected visual acuity (BCVA) in eyes after DSAEK is sometimes limited as compared with a patient's expected potential vision. For DSAEK eyes, the average BCVA ranged from 20/34 to 20/66 with a mean length of follow-up of 9 months (range, 3-21 months).…”
mentioning
confidence: 98%